The interrelationships between television viewing, values and perceived well-being: A global perspective - Smith Speck, Sandra K; Roy, Abhijit (Journal of International Business Studies, 2008)
Do global marketing efforts, for example, those using television as a medium, impact on the values and life satisfaction of people, and, if so, is the process similar or different in various regions of the world? We empirically examine the relationship between television viewing, core values (i.e., religiosity and materialism), and perceived well-being factors (e.g., perceived socioeconomic status and relative life satisfaction). Data collected from the Western developed nations (e.g., United States and New Zealand) and several culturally homogeneous regions, including New Europe, Latin America, the Middle East, and the Far and Southeast, support the prevalence of diverse consumptionscapes with multiple global consumer cultures, rather than a single global culture. Globalization and advances in technology have not created global norms and homogenized our identities, but behavioral patterns and regional identities that are surprisingly durable. Specifically, materialism was shown to influence perceived socioeconomic status both positively (for two regions) and negatively (for two regions), and relative life satisfaction (except in New Europe), while perceived socioeconomic status had a positive influence on relative life satisfaction (except in New Europe and Latin America). The quantity of television viewing was positively shown to influence materialism, directly in some cases, as well as through perceived realism in others, providing limited support for the cultivation theory effect. Finally, religiosity was shown to play a countervailing role in negatively influencing materialism only in Latin American and Middle Eastern countries, and a positive influence on relative life satisfaction only in Latin America. The rationale behind the differences across regions was also explored. The overall results can perhaps be best explained by “postmodern” epistemologies, in which people worldwide are increasingly implicated, and in which new traditions are constantly being invented.